Digital transformation and innovation for enhancing the performance of primary schools in Malaysia - Ibrahim, Abdullah; Jusoh, Mohd Johari; Tahir, Norazura; Hamzah, Shamsida Suriyam Binti; Tasilkhan, Muhajir (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The digital transformation presents a unique and powerful avenue for enhancing the leadership role of headmasters in primary schools in Malaysia. The technological transformation at primary schools has encompassed integrating digital tools to streamline administrative processes, faster communication, and foster decision-making. The purpose of the current study is to find out the effect and the role of the headmaster’s innovative leadership style in utilizing digital tools and adopting the technologies for administrative roles. Furthermore, following the Malaysian Education Quality Standard (MEQS), the headmaster acts as a high-impact leader to mobilize and develop the school community in an integrated manner. The method used in this study is a quantitative method, with a data collection process through a survey of school principals, related to national schools in Kuala Nurus, and the surrounding areas. The findings show that adaptation digital tools enabling the data-driven approach, enhancing administrative efficiency, and improving the communication style facilitate more responsive and positive leadership roles. Therefore, this digital transformational approach ultimately pays for a better educational experience for students, and a more robust and adaptive learning school environment. This study also concluded that more digital transformation adaptation in primary schools will lead to improving the key performance indicators of schools in Malaysia.